2016
DOI: 10.1371/journal.pone.0148891
|View full text |Cite
|
Sign up to set email alerts
|

Association of PON1, P2Y12 and COX1 with Recurrent Ischemic Events in Patients with Extracranial or Intracranial Stenting

Abstract: Background and PurposeShort-term combined use of clopidogrel and aspirin improves cerebrovascular outcomes in patients with symptomatic extracranial or intracranial stenosis. Antiplatelet non-responsiveness is related to recurrent ischemic events, but the culprit genetic variants responsible for the non-responsiveness have not been well studied. We aimed to identify the genetic variants associated with poor clinical outcomes.MethodsPatients with symptomatic extracranial or intracranial stenosis scheduled for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 44 publications
0
24
2
Order By: Relevance
“…Most studies focused on rs2046934 (T744C) or rs6809699 (G52T) representing dbSNP rs10935838, rs2046934, rs5853517 and rs6809699, and rs6785930 (C34T). Some found that it can modulate platelet response to clopidogrel or affect patients' outcomes (Fontana et al, 2003;Zee et al, 2008;Staritz et al, 2009;Shalia et al, 2013;Zoheir et al, 2013;Li et al, 2016), but most results were negative (Angiolillo et al, 2005;Smith et al, 2006;Cuisset et al, 2007;Lev et al, 2007;Bierend et al, 2008;Bonello et al, 2010;Jang et al, 2012;Namazi et al, 2012;Kar et al, 2013;Kim et al, 2013;Jana et al, 2014). Our results show that the P2RY12 allele rs2046934 (T744C) was not significantly associated with HTPR neither in the total study population nor in nonsmokers.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Most studies focused on rs2046934 (T744C) or rs6809699 (G52T) representing dbSNP rs10935838, rs2046934, rs5853517 and rs6809699, and rs6785930 (C34T). Some found that it can modulate platelet response to clopidogrel or affect patients' outcomes (Fontana et al, 2003;Zee et al, 2008;Staritz et al, 2009;Shalia et al, 2013;Zoheir et al, 2013;Li et al, 2016), but most results were negative (Angiolillo et al, 2005;Smith et al, 2006;Cuisset et al, 2007;Lev et al, 2007;Bierend et al, 2008;Bonello et al, 2010;Jang et al, 2012;Namazi et al, 2012;Kar et al, 2013;Kim et al, 2013;Jana et al, 2014). Our results show that the P2RY12 allele rs2046934 (T744C) was not significantly associated with HTPR neither in the total study population nor in nonsmokers.…”
Section: Discussioncontrasting
confidence: 51%
“…As well as CYP2C19, other genetic factors may contribute to the inter-individual variability of clopidogrel, among which P2RY12, which encodes the P2Y12 receptor on platelets, is of importance. Previous studies have implied that P2RY12 single nucleotide polymorphism (SNP) might play a role on the large variability in clopidogrel response, but the results were inconsistent and controversial (Angiolillo et al, 2007;Zee et al, 2008;Jana et al, 2014;Oestreich et al, 2014;Li et al, 2016;Zhang et al, 2016). Most of those studies focused on single haplotype-tagging SNPs (ht-SNPs), such as rs2046934 (i-T744C) or rs6785930, or two common haplotypes H 1 and H 2 (constituted by single nucleotide polymorphism database (dbSNP) rs10935838, rs2046934, rs5853517, and rs6809699), especially the previous studies in the Chinese population (Chen et al, 2014;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Voora et al [29] also investigated the association of PEAR1 polymorphisms with cardiovascular events but failed to find such an association during aspirin treatment in American patients with CAD. Similarly, the association of P2Y12 with recurrent ischemic events in patients with extracranial or intracranial stenting was confirmed [30], but none of the selected SNPs in P2Y12 were associated with adverse outcomes in 426 patients with minor ischemic stroke [31]. Thus, these findings show that the effects of genetic variants on clinical outcomes remain elusive.…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, the present study is the first genome-wide and large-scale association analysis that integrates whole exome and targeted sequencing to identify novel genetic variants associated with MACE in patients with clopidogrel and aspirin treatment after PCI. By combining the two-stage sequencing data, we investigated five commonly reported SNPs [4,[6][7][8][21][22][23] and confirmed PON1 (HR 1.45; P = 0.003) but not CYP2C19 genetic variants contributed to cardiovascular outcomes in Han Chinese patients (Table S10). Moreover, we identified six novel genetic variants associated with MACE: MYOM2 (rs17064642), KRTAP10-4 (rs201441480), WDR24 (rs11640115), ECHS1 (rs140410716), AGAP3 (rs75750968) and NECAB1 (rs74569896).…”
Section: Discussionmentioning
confidence: 99%